2006
DOI: 10.1112/s0024609306018492
|View full text |Cite
|
Sign up to set email alerts
|

Universal Overconvergence and Ostrowski-Gaps

Abstract: We prove that certain universality properties of the partial sums force a power series to have Ostrowski-gaps. This has interesting consequences for some classes of universal functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 10 publications
1
51
0
5
Order By: Relevance
“…Ostrowski gaps were successfully used, for example in [2,4,6,8,21,22,24,27], to obtain certain properties of universal Taylor series with respect to overconvergence. Here, in order to prove our results, Ostrowski gaps will also be our main tool.…”
Section: Ostrowski Gaps and Cesàro Meansmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostrowski gaps were successfully used, for example in [2,4,6,8,21,22,24,27], to obtain certain properties of universal Taylor series with respect to overconvergence. Here, in order to prove our results, Ostrowski gaps will also be our main tool.…”
Section: Ostrowski Gaps and Cesàro Meansmentioning
confidence: 99%
“…K ∩ Ω = ∅, then we have the definitions of the corresponding classes and Functional Analysis we refer to [14,15]. Properties of the universal functions belonging to these classes can be found in [1,2,4,[9][10][11][12]16,19,[23][24][25][26][27][28]30,31]. For example, 26]).…”
Section: Definition 12mentioning
confidence: 99%
“…Melas [13] (see also Costakis [5]) has shown that U ( ; ) 6 = ; for any 2 whenever Cn is compact and connected, and has asked if U ( ; ) can be empty when Cn is compact but disconnected. On the other hand, Müller, Vlachou and Yavrian [15] have shown, for non-simply connected domains , that thinness of the set Cn at in…nity is necessary for U ( ; ) to be non-empty, and have conjectured that this condition is also su¢ cient. There is clearly a large gap between the results of [13] and [15].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Müller, Vlachou and Yavrian [15] have shown, for non-simply connected domains , that thinness of the set Cn at in…nity is necessary for U ( ; ) to be non-empty, and have conjectured that this condition is also su¢ cient. There is clearly a large gap between the results of [13] and [15]. Also there has been no known example of a domain and points 1 ; 2 2 such that U ( ; 1 ) 6 = ; and U ( ; 2 ) = ;.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation